Exploring the links between sensory sensitivity, autistic traits and autism-related eating behaviours in a sample of adult women with eating disorders - Gianmarco Ingrosso; Veronica Nisticò; Francesco Lombardi; Benedetta Morlacchi; Anna Chiara Cigognini; Margherita Oresti; Raffaella Faggioli; Anna Mottaran; Carolina Alberta Redaelli; Martina Tramontano; Laura Ranzini; Simona Anselmetti; et al. (Scientific Reports)
Abstract This study examined the presence of autistic traits in a sample of adult women diagnosed with different Eating Disorders (ED), and explored the concurrent role of autistic traits and sensory sensitivity in influencing both their eating disorder symptomatology and their autism-related eating behaviours. Seventy-five women with different ED (Anorexia Nervosa, Bulimia Nervosa, Binge-Eating Disorder, Other Specified Feeding or Eating Disorder) completed the Eating Attitude Test (EAT-26), the Autism Quotient (AQ), the Ritvo Autism Asperger Diagnostic Scale-Revised (RAADS-R), the Sensory Perception Quotient - Short Form 35 item (SPQ-SF35) and the Swedish Eating Assessment for Autism Spectrum Disorders (SWEAA). Twelve percent of participants scored above the cut-off on both the AQ and the RAADS-R, while 68% scored above the cut-off on the RAADS-R only. A mediation analysis revealed that the association between sensory sensitivity (SPQ-SFR35) and scores on both the EAT-26 and the SWEAA was significantly mediated by the presence of autistic traits (RAADS-R). These findings, first, confirm the presence of autistic traits in individuals with ED; second, they show that a lower sensory threshold (i.e., a higher sensory sensitivity) is associated with a higher presence of autistic traits which were, in turn, positively associated with dysfunctional eating behaviours typical of ED and ASD. This study ultimately highlights the importance of further research on autistic traits across all diagnostic categories of ED.